Does adherence to antiretroviral therapy differ by place of residence in Nigeria? A systematic review and meta-analysis protocol - Badru, Oluwaseun Abdulganiyu; Bain, Luchuo Engelbert; Adeagbo, Oluwafemi Atanda (BMJ open, 2023)
IntroductionRetention in care is still a significant challenge in the HIV treatment cascade and varies extensively across regions, leading to poor adherence to antiretroviral therapy (ART). Several factors across different socioecological levels, such as health and community-level factors, inhibit ART adherence among people living with HIV (PLWH) in Nigeria. This review seeks to ask whether adherence to ART differs by place of residence in Nigeria.Method and analysisThis systematic review and meta-analysis will follow the updated Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. We will search PubMed, SCOPUS, CINAHL, Web of Science, MEDLINE (Ovid) and Google Scholar from onset to 30 April 2023. We will include only quantitative observational studies or mixed-method studies that measured the association between place of residence (urban and rural) and adherence to ART among PLWH aged ≥15 years. Title and abstract screening, full-text screening, data extraction and quality assessment will be done by two reviewers independently. A third reviewer will resolve disagreements. We will extract the author’s name and year of publication, study aim(s), participant’s characteristics, sample size, sampling method, region and state, adherence definition and adherence level in urban and rural areas. Data will be analysed with Review Manager V.5.4. The Q statistical test will be used to assess between-study heterogeneity, while Higgins and Thompson’s I2 will be used to quantify the heterogeneity level. Several subgroups and sensitivity analyses will be conducted.Ethics and disseminationEthical approval is not warranted for this study since primary published data will be utilised. The findings of this review will be published in a high-impact peer-reviewed journal and presented at a conference.PROSPERO registration numberCRD42022371965.